A Novel Multi-analyte Serum Panel Combining CA-125, HE4, microRNA-200a, and Interleukin-6 for the Preclinical Detection of High-Grade Serous Ovarian Carcinoma in Women with Pathogenic *BRCA1/2* Variants: Serum CA-125, HE4, microRNA-200a, and Interleukin- Serous Ovarian Carcinoma - Li, Chanyu; Yang, Zhiling; Xie, Jiaqiong; Long, Yingfei (Journal of Medical Biochemistry, 2026)
Background: Pathogenic *BRCA1/2* variant carriers require effective surveillance for high-grade serous ovarian cancer (HGSOC), a malignancy characterized by late-stage detection and poor prognosis. Current monitoring with CA-125 and transvaginal ultrasound lacks sensitivity for early-stage disease. Objective: To develop and validate a multi-analyte serum panel for the preclinical detection of HGSOC in *BRCA1/2* carriers. Methods: In a prospective, multicenter longitudinal cohort, we enrolled 450 women with pathogenic *BRCA1/2* variants. Serial serum samples were collected every 6 months. The study included 45 incident HGSOC cases and 405 matched controls. Levels of CA-125, HE4, miR-200a, and IL-6 were quantified using immunoassays and RT-qPCR. A composite risk score was derived using logistic regression, and diagnostic performance was evaluated using ROC curve analysis, sensitivity, specificity, and lead-time assessment. Results: All four biomarkers were significantly elevated in pre-diagnostic samples from HGSOC cases (p<0.001). The combined panel achieved an AUC of 0.95 (95% CI: 0.92-0.98), significantly outperforming individual markers (CA-125 AUC=0.86; HE4 AUC=0.82; miR-200a AUC=0.88; IL-6 AUC=0.70; DeLong’s test p<0.01). At a 90% specificity threshold, the panel’s sensitivity was 88%, compared to 68% for CA-125 alone. The panel detected HGSOC a median of 12 months (IQR: 8-16) prior to clinical diagnosis, with a lead-time sensitivity of 72% at 18 months pre-diagnosis. Conclusion: The integrated serum panel of CA-125, HE4, miR-200a, and IL-6 demonstrates exceptional diagnostic accuracy for the preclinical detection of HGSOC in BRCA carriers. This panel represents a transformative potential for structured surveillance programs, enabling earlier intervention and personalized risk management.